ECONOMIC STRUCTURE ANALYSIS, LEADING SECTORS AND REGIONAL DEVELOPMENT IN MALANG YEAR 2008-2012. - Seno Aji Santoso (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2014)
The purpose of this study was to determine the structure of the economy, the dominant sector and regional development strategies in Malang Year 2008-2012.From the analysis it can be concluded that by using a tool known for Economic Structural Analysis of 9 existing economic sector in Gross Domestic Product during the years 2008 to 2012 the sector that contributes most to the Gross Domestic Product (GDP) at constant prices Malang is the sector tertiary contributing 64.82 %. From the analysis of the leading sectors, Malang has a leading sectors are trade, hotels, and restaurants with LQ value of 1.29 and a differential value shift by shift proportional 195,272.27 and 135,101.68. From the analysis of gravity, Malang has the greatest interaction with the Malang region. For the development of Malang area is quite well characterized by an increase in Gross Domestic Product (GDP) from year to year but still needs to be developed further other economic sectors that still have the potential to compete with other regions in East Java.